2022
DOI: 10.56013/axi.v7i1.1187
|View full text |Cite
|
Sign up to set email alerts
|

Level Berpikir Probabilistik Siswa SMPN 4 Kepanjen

Abstract: This study aims to classify student responses in dealing with probabilistic problems according totheir level, analyze, and identify indicators at each level. This study used a descriptivequalitativeapproach with data collection techniques in the form of tests and interviews which were tested on 66 seventh grade students as research subjects. The results showed that 28 students were at the subjective level, 30 students were at the transitional level, and 8 students were at the informal quantitative level, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…The large amount of information currently expressed in terms of uncertainty has resulted in the importance of probabilistic thinking abilities. Previous research related to probabilistic thinking centered on determining the level of probabilistic thinking at various levels of education, starting from elementary school to college (Fa'ani et al, 2016;Raya, 2017;Raya et al, 2021;Sari et al, 2023;Sari et al, 2017;2018a;Shodiqin et al, 2021;. The research results found that students' probabilistic thinking tends to be low and is often at a level below their age.…”
mentioning
confidence: 89%
“…The large amount of information currently expressed in terms of uncertainty has resulted in the importance of probabilistic thinking abilities. Previous research related to probabilistic thinking centered on determining the level of probabilistic thinking at various levels of education, starting from elementary school to college (Fa'ani et al, 2016;Raya, 2017;Raya et al, 2021;Sari et al, 2023;Sari et al, 2017;2018a;Shodiqin et al, 2021;. The research results found that students' probabilistic thinking tends to be low and is often at a level below their age.…”
mentioning
confidence: 89%